Pengaruh Citra Merek Terhadap Keputusan Calon Mahasiswa Memilih Kampus Dengan Persepsi Kualitas Sebagai Variabel Interveing - Suhroji Adha; Irawan Irawan (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study was conducted to analyze the influence of brand image on the decision to choose a campus by taking the perception of quality as an intervening variable. This research was conducted. A sample of 100 students from the University of Faletehan was taken using a convenience sampling/accidental sampling technique. The data analysis method uses the SEM method, namely smart PLS.